Bimetallic silver-gold film waveguide surface plasmon resonance sensor - Ong, Biow Hiem (2009)
It is desirable that a surface plasmon resonance (SPR) sensor is highly sensitive to binding interactions within the sensing region, generate evanescent fields with long penetration depths, and utilize a metal film that is very stable even in extreme environmental conditions. In this study, we present the first example of a wavelength-modulated waveguide SPR sensor with a bimetallic silver-gold film for surface plasmon excitation. The underlying silver yields better evanescent field enhancement of the sensing surface, while the overlying gold ensures that the stability of the metallic film is not compromised. It is shown experimentally that in terms of dλ/dn, the bimetallic film waveguide SPR configuration has a sensitivity of 1232 nm/RIU, greater than two times improvement from the 594 nm/RIU achievable with single gold film waveguide SPR sensor. The higher sensitivity, compact nature, and better evanescent field enhancement of this configuration provides the potential to biosensing applications.